2008
DOI: 10.1007/s10311-008-0192-8
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of CuO/SiO2 and photocatalytic activity by degradation of methylene blue

Abstract: A photocatalyst based on CuO/SiO 2 was prepared, and evaluated for the degradation of methylene blue in aqueous medium. The photocatalyst was obtained by calcination method of copper salt, in the presence of silica. The characterization by XRD, FTIR, and TPR techniques confirmed the formation of CuO as active phase. SEM studies showed CuO deposited on the surface of SiO 2 . By ESI-MS, it was demonstrated that the degradation of methylene blue occurs through successive hydroxylations. Photodegradation assays sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(33 citation statements)
references
References 15 publications
0
28
1
4
Order By: Relevance
“…This is in contrast to 94% degradation ratio of MB obtained with CuO/X zeolite heterogeneous catalyst and reaction time of 3 h [58]. The degradation ratio is also higher than that reported values obtained under UV light irradiation with CuO/SiO 2 photocatalyst [59], spindly CuO microstructure [60] and ZnO nanoparticles [61], although the rigid comparison of the catalytic activities among them is difficult because of the different test system and parameters [62]. This photocatalytic result demonstrates that the porous CuO superstructure would be used as a potential photocatalyst, which can operate under visible light irradiation.…”
Section: Photocatalytic Propertiescontrasting
confidence: 78%
See 1 more Smart Citation
“…This is in contrast to 94% degradation ratio of MB obtained with CuO/X zeolite heterogeneous catalyst and reaction time of 3 h [58]. The degradation ratio is also higher than that reported values obtained under UV light irradiation with CuO/SiO 2 photocatalyst [59], spindly CuO microstructure [60] and ZnO nanoparticles [61], although the rigid comparison of the catalytic activities among them is difficult because of the different test system and parameters [62]. This photocatalytic result demonstrates that the porous CuO superstructure would be used as a potential photocatalyst, which can operate under visible light irradiation.…”
Section: Photocatalytic Propertiescontrasting
confidence: 78%
“…It is well documented that dye pollutants such as rhodamine B [5,55,56], methylene blue can be photodegraded under ultraviolet or visible light with the catalytic action of metal oxide such as ZnO and TiO 2 [57][58][59]. The photocatalytic activity of our obtained CuO superstructures in the degradation of well-known organic dye MB, a typical pollutant in the textile industry, was then evaluated in the presence of hydrogen peroxide.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%
“…The catalytic activities of PNA complexes have been reported with Ni (II) and Co (II) ions for biosensor applications with NADH/ NAD redox system [164]. Ameen et al [165] reported the synthesis of novel PNA/SiO 2 and PNA/TiO 2 nanocomposites for the photocatalytic degradation of methylene blue (MB) dye.…”
Section: Nanocomposites Of Poly(1-naphthylamine)/sio 2 and Poly(1-napmentioning
confidence: 99%
“…CuO has thus been applied as a Fenton-like catalyst [14][15][16] . Most of the work done were with CuO nanoparticles and the degradation efficiencies achieved were not impressive [17][18][19][20][21][22][23][24] . One-dimensional (1D) CuO nanostructures have also been applied as photo-degradation catalysts and showed promising performances [25,26] .…”
Section: Introductionmentioning
confidence: 99%